Manipulation of diacylglycerol and ERK-mediated signaling differentially controls CD8+ T cell responses during chronic viral infection - Harabuchi, Shohei; Khan, Omar; Bassiri, Hamid; Yoshida, Taku; Okada, Yohei; Takizawa, Masaomi; Ikeda, Osamu; Katada, Akihiro; Kambayashi, Taku (Frontiers in Immunology, 2022)
Activation of T cell receptor (TCR) signaling is critical for clonal expansion of CD8+ T cells. However, the effects of augmenting TCR signaling during chronic antigen exposure is less understood. Here, we investigated the role of diacylglycerol (DAG)-mediated signaling downstream of the TCR during chronic lymphocytic choriomeningitis virus clone 13 (LCMV CL13) infection by blocking DAG kinase zeta (DGKζ), a negative regulator of DAG. Upon LCMV CL13 infection, the enhancement of DAG signaling by DGKζ deficiency promoted early short-lived effector cell (SLEC) differentiation of LCMV-specific CD8+ T cells, but this was followed by abrupt cell death. Short-term inhibition of DGKζ with ASP1570, a DGKζ-selective pharmacological inhibitor, augmented CD8+ T cell activation without causing cell death, which reduced virus titers both in the acute and chronic phases of LCMV CL13 infection. Unexpectedly, the selective enhancement of ERK, one key signaling pathway downstream of DAG, lowered viral titers and promoted expansion, survival, and a memory phenotype of LCMV-specific CD8+ T cells in the acute phase with fewer exhausted T cells in the chronic phase. The difference seen between DGKζ deficiency and selective ERK enhancement could be potentially explained by the activation of the AKT/mTOR pathway by DGKζ deficiency, since the mTOR inhibitor rapamycin rescued the abrupt cell death seen in virus-specific DGKζ KO CD8+ T cells. Thus, while ERK is downstream of DAG signaling, the two pathways lead to distinct outcomes in the context of chronic CD8+ T cell activation, whereby DAG promotes SLEC differentiation and ERK promotes a memory phenotype.